PEACE AND REMEMBRANCE IN INDEPENDENT UZBEKISTAN - Ismoilova Asila; Abdujabborova Iroda (Ustozlar uchun, 2025)
This article discusses Uzbekistan’s efforts since gaining independence to promote peace and stability both globally and within the Central Asian region. It emphasizes the peaceful resolution of conflicts, the role of humanitarian operations, and the nationwide celebration of “Remembrance and Appreciation Day” on May 9. On this day, the memory of brave and resilient individuals who perished during the war and labor front from 1941 to 1945 is honored. Special attention is also given to showing care for elderly veterans and supporting them in every way possible.